MANAJEMEN KEGIATAN BELAJAR MENGAJAR PENDIDIKAN KARAKTER BANGSA DENGAN MENGGUNAKAN MEDIA BATIK PADA SDN PURO PAKUALAMAN 1 YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research aims to describe the planning, the organization, the implementation, and the evaluation of national character building through batik. This research was a descriptive-qualitative research which refers to phenomenological perspective and naturalistic. Data collecting method used observation, documentation, and interview. Data analyzing method used domain and theme analysis by studying, analyzing, interpreting the data and drawing conclusion. This research results shows that: (1) the planning of the management has met the standard of good management, although has not been complete yet. It contains supporting policy, good finance, curriculum which integrates national character education. (2) The organizing management of the national character education is good enough. The job description, responsibility, and authority are established in school meeting. On occasion of national character building through batik, has been tried to be done optimally. It is shown by the engagement of the school professional staff to the teaching-learning process (3) the school principal applies democratic leadership system. Each decision is always discussed by the school principal together with the school staff and committee. (4) On occasion of evaluation, SDN Puro Pakualaman 1 makes the correction to improve the result.